Testing Overall and Synergistic Campaign Effects in a Partisan Statewide Election. (June 2018) - Shaw, Daron; Blunt, Christopher; Seaborn, Brent
Although studies based on field experiments and large- N surveys have enhanced our understanding of how campaigns affect U.S. elections, few of these projects have (1) considered the synergistic effects of distinct aspects of the campaign, (2) focused on statewide, partisan elections, or (3) considered the durability of any estimated campaign effects. We rely on a massive field experiment from the 2014 Texas gubernatorial campaign to assess the individual, synergistic, and collective impact of a variety of outreach modes on the electorate. The data demonstrate some durable synergistic and overall campaign effects on voters' attitudes toward the sponsoring candidate, with lesser effects on turnout. In addition, while the results indicate that television is rightly considered the most effective mover of voters, radio and Internet advertising also have notable effects and may, in fact, deliver a better return on investment.